Một phương pháp đo lực cắt khi mài - Lê, Văn Tiến (Hà Nội, 2013)
The measurement of cutting force of grinding is necessary to study dynamica of grinding process. This article shows the method for the measurement of cutting force of grinding, which is being used on the faculty of Mechanical Technology and Mechanical Precision of the Ha noi Universty of Technology.